A Two-Step Femtosecond Laser-Based Deposition of Robust Corrosion-Resistant Molybdenum Oxide Coating - Ali, Asghar (2023)
A two-step femtosecond-pulsed laser deposition (fs-PLD) process is reported for the rapid development of uniform, poreless, crack-free, and well-adhering amorphous coatings of source materials with a high melting point. The first step comprises a high-rate raw deposition of the source material via fs-PLD, followed by a second step of scanning the raw sample with fs laser pulses of optimized fluence and scan parameters. The technique is applied to develop substoichiometric molybdenum oxide (MoOx, x < 3) coatings on mild steel. The thickness of the layer was ~4.25 μm with roughness around 0.27 μm. Comprehensive surface characterization reveals highly uniform and relatively moderate roughness coatings, implying the potential of these films as robust corrosion-resistant coats. Corrosion measurements in an aqueous NaCl environment revealed that the coated mild steel samples possess an average corrosion inhibition efficiency of around 95% relative to polished mild steel.